A resolver-to-digital conversion method based on third-order rational fraction polynomial approximation for PMSM control - Wang, Shuo; Kang, Jinsong; Degano, Michele; Buticchi, Giampaolo (IEEE, 2018)
In this paper, a cost-effective and highly accurate resolver-to-digital conversion (RDC) method is presented. The core of the idea is to apply a third-order rational fraction polynomial approximation (TRFPA) for the conversion of sinusoidal signals into the pseudo linear signals, which are extended to the range 0-360° in four quadrants. Then, the polynomial least squares method (PLSM) is used to achieve compensation to acquire the final angles. The presented method shows better performance in terms of accuracy and rapidity compared with the commercial available techniques in simulation results. This paper describes the implementation details of the proposed method and the way to incorporate it in digital signal processor (DSP) based permanent magnet synchronous motor (PMSM) drive system. Experimental tests under different conditions are carried out to verify the effectiveness for the proposed method. The obtained maximum error is about 0.0014° over 0-360°, which can usually be ignored in most industrial applications